Exploring Multiple Dimensions of Recording Video Clips in Group in Learning English Speaking Skill - Nguyen Chau Bich , Tuyen (International Journal of Scientific Research and Management (IJSRM), 2020)
Applying technology in learning English language is indispensable in the period of industry 4.0 and global integration. However, what technological techniques should be applied in teaching and learning process is the most serious concern. Evidence shows that different technological applications may lead to various learning outcomes, detrimental effects, even spoiling learning interest or motivations. Therefore, this paper is aimed not only to explore the multiple dimensions of recoding video clips in group (RVCIG) in learning English speaking skill but also illustrate how this activity (RVCIG) influences on learners’ English speaking  improvement. Apparently, these explorations and illustrations help to consider whether this RVCIG is widely used in teaching English speaking process or not. To do that, a quantitative research method with the tool of semi - structure interview is used to collect various information, mixed feedbacks or motivations from 2 groups of students fully participating in recording three video clips in group within course. Additionally, a questionnaire survey is also sent to 33 English learners for exploring both commendable and detrimental influences of this RVCIG on English speaking development. The findings indicate that RVCIG makes learners have various opposite experiences in language competence, confident expression, and communication, as well as cope with unavoidable challenges of time consuming, technological problems, and group member’ disagreements. Whatever advantages or disadvantages of this RVCIG activity has, learners also express their interest and expectation of recording video clips in group for purposes of English speaking improvement, mutual engagement, collaborative learning and building friendship.